Extraction and Characterization of Melanin Pigment from Local Isolated Pseudomonas aeruginosa - Naz Fuad Hama Khorshid; Nisreen Hadi Odaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
In this present study, a clinically isolated of Pseudomonas spp. from a variety of sources, such as burn patients, wound infections, and UTI patients, that can produce melanin pigment in the presence of 2 % L-tyrosine in both liquid and solid media. These bacteria were identified as Pseudomonas aeruginosa based on morphological, biochemical, and VITEK-2 compact system analysis. The higher melanin producer isolate Ps81, which produces melanin at rate of 3.018933 µg/ml, has been chosen for further investigation steps. The pigment was extracted by several steps of alkali dissolving and acid precipitation followed by washing with organic solvents. Chemical analysis of the pigment particles revealed that they were acid resistant, alkali soluble, insoluble in water, soluble in methanol 100%, ethanol 70% and DMSO but insoluble in ethyl acetate and chloroform. The alkali melanin solution displayed a significant UV absorbance at 273.5 nm and decreased toward visible light and infrared region, the pigments UV-visible spectrum ranged from 200 to 800 nm. FT-IR spectroscopy was used to further characterize the melanin pigment. The infrared spectrum of purified melanin extracted from Ps 81 exhibited a broad absorption band around 3280.82 cm−1 which correspond to the presence of -OH group and N-H groups.